GEOPOLITICAL AND GEOECONOMIC ASPECTS OF THE KAZAKHSTAN’S FOREIGN POLICY IN THE CONDITIONS OF NEW GLOBAL REALITY - G.M. Duisen,; D.A. Aitzhanova, (Academic Journal of Physical and Chemical Sciences, 2019)
This article discusses the geopolitical and geo-economic position of the Republic of Kazakhstan at the present stage, as well as the place of the Republic of Kazakhstan in the international arena. The authors noted the special role and place of our country at the regional and international levels. The analysis of the dynamics of foreign trade turnover and attracting investment in the domestic economy. In the conclusion of the work, conclusions were made about the need to improve Kazakhstan’s foreign policy towards multi-vector approach and national security, which is achievable through scientifically-based and balanced political diplomacy.